Maxilla bone pre-surgical evaluation aided by 3D models obtained by rapid prototyping - Queijo, Luis (2010)
For implant planning and placement, the association of CAD and CAM techniques furnishes some advantages, regarding 3D determination of the patient’s jaw anatomy and fabrication of both anatomical models and surgical guides (Verstreken et al. 1996). In this paper we will present Rapid Prototype (RP) use as a tool, able to produce solid models of a maxilla in order to allow pre-surgical conditions evaluation in a pa-tient who has lost bone tissue and needs dental implants. In this process, three-dimensional reconstruction has been made from a bi-dimensional image file, obtained by Computerized Tomography (CT) and a set of partial and total biomedical models have been manufactured to allow maxilla analysis. Rapid Prototyping technique used has been three-dimensional printing (TDP or 3DP) which allows a good reality simulation.